Investigating Exposure to Community Violence and Associated Internalizing and Externalising Behaviours in a Sample of South African Male Youth - Goolam Nabi, Zayaan (Department of Psychology, 2023)
Exposure to community violence has been acknowledged as a public health problem, affecting individuals' mental well-being and health. Community violence refers to incidents of violence which take place within an individual's community or outside an individual's home. Research exploring the behavioural and emotional outcomes of exposure to community violence has suggested that youth with high levels of exposure to community violence may exhibit adverse emotional and behavioural outcomes. Although there is a large body of literature exploring exposure to community violence, there is a dearth of South African (SA) literature looking at exposure to community violence in terms of being a victim, witness or perpetrator of community violence and the associated outcomes. Existing research does not consider the impact of community violence on all three levels (and especially so with regards to perpetration of violence) in relation to internalizing and externalizing behaviours and callous-unemotional traits in male youth, thus presenting an area for research inquiry. Using a cross-sectional, quantitative design, the current study investigated exposure to community violence and its three subcategories, namely, witness, victim or perpetrator and the associated callous-unemotional traits, internalising and externalising behaviours in a sample of SA male youth (N =108) through a range of self-report measures (Alcohol Use Disorders Identification Test; Alcohol, Smoking, and Substance Involvement Screening Test; Beck Depression Inventory-Second Edition; Child Behaviour Checklist Youth Self-Report; Child Exposure to Community Violence Checklist; Inventory of Callous-Unemotional Traits; Maudsley Addiction Profile and Reactive-Proactive Aggression Questionnaire). Results indicated that not all three subcategories of exposure to community violence were significant predictors of the outcome variables. The results of the regression analyses showed: exposure to community violence and its three subcategories as significant predictors of the externalizing behaviour syndrome grouping, and of depressive symptoms and withdrawn/depressed symptoms in terms of internalising behaviours; exposure to community violence and being a witness and victim of violence as significant predictors of the internalizing behaviour syndrome grouping, and anxious/depressed symptoms and somatic complaints within this grouping; exposure to community violence and being a victim and perpetrator of violence as significant predictors of aggression and reactive aggression (externalising behaviours); exposure to community violence as a perpetrator as a significant predictor of proactive aggression (externalising behaviour); and exposure to community violence and being a witness and perpetrator of violence as significant predictors of rule breaking behaviour (externalising behaviour), with significance rates ranging from p < .05 to p < .001. Notably, callous-unemotional traits were not significantly correlated to any study variables. The current study is largely aligned with existing research and how both internalizing and externalizing behaviours may co-occur in relation to the three levels of exposure to community violence. Further research on callous-unemotional traits in relation to community violence is needed. As community violence occurs in various contexts understanding the associated adverse outcomes at all three levels of exposure may assist the development of interventions and policy initiatives which can prevent further experiences of victimization and perpetration of community violence by male youth.